Acupuncture Clinical Trials on Knee Osteoarthritis - Gong, Changzhen (Chinese medicine and natural products, 2023)
The outcomes of eight acupuncture clinical trials on knee osteoarthritis were published in well-regarded English-language mainstream medical journals between 1975 and 2022. Reported trial results were equally balanced between positive and negative outcomes, thus producing an overall impression of ambiguity in regard to the efficacy of acupuncture in the treatment of knee osteoarthritis. This paper reviews these trials, analyzes the factors taken into account in each trial, and has posited two reasons for the continuing lack of consensus in regard to the medical effectiveness of acupuncture: the difficulty of designing scientifically consistent clinical-trial studies; and an institutional bias toward ambiguity on the part of scientific and medical journals.
Keywords: knee osteoarthritis; acupuncture; clinical trials; sham control; medical journals; institutional bias